Fred Nuttall (1900-1988) - Fisher, Edward J. (Canadian Journal of Optometry, 2026)
The death of Fred Nuttall brings to mind once again the tremendous dept which present day optometrists owe to those pioneers who sacrificed so very much of their personal time and fortune very freely, in order that Optometry might reach its present level of success and public recognition. Many present day optometrists may ask "Who was Fred Nuttall anyway?" Let me try to fill in some of the strides Optometry has taken because of Fred Nuttall and others of his generation.